Changes in Cell Wall Structure During Rhizoid Formation of Silvetia babingtonii (Fucales, Phaeophyceae) Zygotes. Issue 4 (26th May 2021) - Yonamine, Rina; Ichihara, Kensuke; Tsuyuzaki, Shiro; Hervé, Cécile; Motomura, Taizo; Nagasato, Chikako
Abstract : We examined the ultrastructure of the cell wall and immunolocalization of alginates using specific antibodies against M‐rich alginates and MG blocks during rhizoid formation in fucoid zygotes, Silvetia babingtonii . The thallus region of 24‐h‐old zygotes had a cell wall made of three layers with different fiber distribution. In the 12‐h‐old zygotes, three layers in the thallus were observed before rhizoid formation, namely the inner, middle, and outer layers. During rhizoid elongation, only the inner layer was apparent close to the rhizoid tip area. Immunoelectron microscopy detected M‐rich blocks of alginate on the inner half of the cell wall, irrespective of the number of layers in the thallus and rhizoid regions. The MG blocks were seen to cover a slightly wider area than M‐rich alginate blocks. It was suggested that parts of M in mannuronan would be rapidly converted to G, and MG‐blocks are generated. Transcriptome analysis was performed using 3 ‐, 10 ‐, and 24‐h‐old zygotes after fertilization to examine the relationship between gene expression and alginate synthesis over time. The expression of two mannuronan C5‐epimerase homologs that convert mannuronic acid into guluronic acid in alginates was upregulated or downregulated over the course of the examination.